An Analysis of Grade VIII Students' Difficulties in Solving Circle Story Problems: A Study Based on Polya's Problem-Solving Theory - Septianingsi Manekat; Aloisius Loka Son; Meiva Marthaulina Lestari Siahaan (S&Co Publishing, 2025)
This study aims to explore the difficulties experienced by students of grade VIII of junior high school in solving circle story problems based on Polya's Theory. The research approach used is a qualitative approach. This type of research is qualitative descriptive research. This research was conducted in one of the junior high schools in North Central Timor Regency. The subjects of this study were grade VIII consisting of 20 students. The instruments used were 4 circle material test questions and interviews to determine the factors that cause students to have difficulty working on the questions. Data analysis techniques through the stages of test data analysis, data reduction, data display and conclusion drawing. The results of this study indicate that the difficulties faced by students are 1) difficulty understanding the problem, namely students have difficulty in positioning the function of the symbol on the known and asked parts of the question, 2) difficulty making a solution plan, namely students have difficulty connecting the known and asked elements so that students do not fully understand the strategy that will be used to plan the solution, 3) difficulty completing the solution plan, namely students have difficulty writing a complete formula to be used in solving the problem so that they do not find the results requested by the question, 4) difficulty re-checking, namely students do not know how to make conclusions from the results of their work.